Asymmetric Organocatalysis with Chiral Covalent Organic Frameworks - Song-Chen Yu; Liang Cheng; Li Liu (Organic Materials, 2021)
Abstract Inspired by Mother Nature, the use of chiral covalent organic frameworks as heterogeneous asymmetric organocatalysts has arisen over the last decade as a new method in enantioselective synthesis. In this Short Review, sophisticated design of these polymeric materials and their application in asymmetric organocatalysis will be discussed.